2020
DOI: 10.1186/s12880-020-00447-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of contrast-enhanced ultrasonography for large cell neuroendocrine carcinoma in the urinary bladder: a case report

Abstract: Background: Large cell neuroendocrine carcinoma (LCNEC) of the urinary bladder is an uncommon malignant bladder tumor, and the overall prognosis is poor. Contrast-enhanced ultrasound (CEUS) provides a new effective modality for tumor detection and diagnosis. Case presentation: A 30-year-old man complained of repeated painless gross haematuria for half a month. Conventional ultrasound demonstrated a hypoechoic solitary lesion with hyperechoic margins measuring 3.4 × 3.1 cm in the anterior wall of the bladder. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Fewer than 50 sporadic cases have been reported in the literature so far, including both pure and mixed histology. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Nevertheless, since this tumor has been recently recognized as a distinct entity, it has been suggested that some urinary LCNECs might have gone underdiagnosed or just misdiagnosed as undifferentiated UC. 7 Similar to lung tumors, underdiagnosis and consequent underreporting remain an issue also in bladder cancer if appropriate diagnostic workup is not performed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fewer than 50 sporadic cases have been reported in the literature so far, including both pure and mixed histology. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Nevertheless, since this tumor has been recently recognized as a distinct entity, it has been suggested that some urinary LCNECs might have gone underdiagnosed or just misdiagnosed as undifferentiated UC. 7 Similar to lung tumors, underdiagnosis and consequent underreporting remain an issue also in bladder cancer if appropriate diagnostic workup is not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SmCC, LCNEC is a biologically aggressive NE tumor, usually associated with a dismal prognosis despite an aggressive treatment. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]34 Most clinical studies have analyzed both SmCCs and LCNECs, the latter comprising a small amount of the whole case series, and reported similar survival and cancer-specific mortality rates in LCNEC compared with SmCC, ranging from <1 year for advanced disease to > 2 years for early disease. 7,12,15,16 Bhatt et al 10 reported a 5-year survival rate of 17% for their study population, which consisted of 14 SmCCs and only 4 LCNECs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations